Psychosocial Problems and Physical Activity at Different Ages in Patients with Epilepsy - Elvyra Grinienė; Viktorija Pečinina (Lithuanian Sports University, 2018)
Research background and hypothesis. Physical inactivity of patients with epilepsy is associated with the course of the disease, treatment, preconceived attitudes and myths that their physical activity might be dangerous and cause seizures (Steinhoff et al., 1996; Nakken, 2001 ). The aim of our research was to examine the links between the psychosocial problems of patients' with epilepsy, their hysical activity, self-reported quality of life as well as their connection with patients' age. Research  methods.  The  participants  were  209  patients  with  epilepsy  from  three  different  regions  (Šiauliai, Panevėžys and Pasvalys) of Lithuania. The subjects were selected with the help of quantitative closed-type survey - QOLIE-89 and IPAQ international questionnaire. The research findings were compared between two age groups: younger (20-39 years of age) and senior (40-59 years of age) subjects. Research results. The main psychosocial problems for patients with epilepsy were concerns about possible injuries during the seizures, experience of shame and other social restraint, health problems that might occur as a result of taking antiepileptic drugs for a long period of time, negative effects of antiepileptic drugs and memory impairments. These problems were more common among younger respondents (p < 0.05). Physical activity levels in patients with epilepsy were inadequate and different. The main factor that contributed to these differences was patients' age. Younger respondents trained more in their leisure time, while seniors spent more time reading or sleeping (p = 0.002).Younger patients lacked knowledge about the most appropriate types of physical activities, senior  respondents  were  inactive  were  to  the  disapproval  of  medical  professionals  and  their  health  problems   (p = 0.006). Younger respondents evaluated their lifestyle as good enough more often than seniors. Discussion  and  conclusion.  Psychosocial  problems  and  physical  inactivity  of  patients  with  epilepsy  were connected with their age. Younger respondents more often than seniors were physically active and their self-reported quality of life was good. Keywords: age of patients with epilepsy, social problems, physical activity, evaluation of lifestyle.